The King’s Brief Interstitial Lung Disease (KBILD) questionnaire: an updated minimal clinically important difference - Sinha, Aish (BMJ Open Respir Res, 2019)
INTRODUCTION: The King’s Brief Interstitial Lung Disease (KBILD) is a 15-item validated health-related quality of life (HRQOL) questionnaire. The method of scoring the KBILD has recently changed to incorporate a logit-scale transformation from one that used raw item responses, as this is potentially a more linear scale. The aim of this study was to re-evaluate the KBILD minimal clinically important difference (MCID) using the new logit -transformed scoring. METHODS: 57 patients with interstitial lung disease (17 idiopathic pulmonary fibrosis, IPF) were asked to complete the KBILD questionnaire on two occasions in outpatient clinics. At the second visit, patients also completed a 15-item global rating of change of health status questionnaire (GRCQ). The MCID was calculated as the mean of four different methods: the change in KBILD for patients indicating a small change in GRCQ, patients with a 7%–12% change in FVC, 1 SE of measurement of baseline KBILD and effect size (ES) of 0.3. RESULTS: The mean (SD) KBILD total score for all patients was 55.3 (15.6). 16 patients underwent a therapeutic intervention. 36 patients reported a change in their condition on the GRCQ; 22 deteriorated, 14 improved and 21 were unchanged. There was a significant change in KBILD total score in patients reporting a change in GRCQ; mean (SD) 57.0 (13.6) versus 50.0 (9.7); mean difference 7.0; 95% CI of difference 3.0 to 11.0; p<0.01. The change in KBILD total score correlated with the GRCQ scale; r=−0.49, p<0.01. The mean KBILD total score MCID was 5. The MCID of KBILD domains were 6 for Psychological, 7 for Breathlessness and Activities, and 11 for Chest Symptoms. CONCLUSION: The KBILD is a responsive tool for longitudinal assessment of HRQOL in patients with ILD. The MCID of the KBILD total score is a 5-unit change.